Spatial analysis of perceived logistics and traffic impacts from chinese tourist on Nimmanahaeminda residents - Roongsaprangsee C. (2017)
© ExcelingTech Pub, UK. This study aims to assess the perceived logistics and traffic impacts of Chinese tourists in Nimmanahaeminda, Chiang Mai, Thailand. However, As far as we concerns, the study that include spatial literature about evaluation on percerived impacts of locals has not been found. This paper, therefore, focus on the spatial analysis of residents' attitude about these issues by investigating each tract of Nimmanahaeminda's area. Quantum Geographic Information System (QGIS) was employed to illustrate the perception of residents on the logistics and traffic impact influenced by Chinese tourists. Moreover, this study also used Structural Equation Model (SEM) to estimate overall logistics and traffic impacts of the community in order to demonstrate the current situation for the government and other administrations to find the solution together.